Aplicación del proceso de atención de enfermería en un paciente con cardiopatía isquémica - Navarrete Posligua, Jomira Andreina (2018)
Ischemic heart disease is a heart disease caused by a secondary pathophysiological alteration due to an imbalance between the demand and oxygen supply of the heart muscle, one of the main causes of ischemic heart disease is atherosclerosis due to a hardening of the arteries, in which this significantly hinders blood circulation. It is established that ischemic heart disease is the leading cause of death in the world. The World Health Organization conducted an investigation that shows that cardiovascular diseases are the leading causes of death in Ecuador, it is reported that ischemic heart disease belongs to 10.3% of deaths. Among the characteristic symptoms of this pathology are: angina pectoris, pain in the neck or jaw, pain in the shoulder or arm, progressive dyspnea of mid to small effort, diaphoresis and arrhythmic tachycardia. Among the main factors that trigger ischemic heart disease is: Age, smoking, high blood pressure, diabetes mellitus and dyslipidemia. The disease of ischemic heart disease represents an area of opportunity for the professional work of Nursing, through the participation of the specialized nursing process. The Nursing model used in this clinical case study was Dorotea Orem's self-care deficit theory, which defines the objective of nursing as: "To help the individual maintain and carry out self-care actions on his / her own so that You can also preserve your health and your own life, It also describes and explains the reasons why individuals subject to limitations can not assume self-care, determine when and why the intervention of the nurse is needed. Nursing allows us to evaluate the physical and mental state of the patient through a physical examination, establish nursing diagnoses, and develop care plans using the NANDA, NOC, and NIC taxonomy.